1999
DOI: 10.1152/ajpcell.1999.276.5.c1139
|View full text |Cite
|
Sign up to set email alerts
|

P2Z/P2X7receptor-dependent apoptosis of dendritic cells

Abstract: Macrophages and thymocytes express P2Z/P2X7nucleotide receptors that bind extracellular ATP. These receptors play a role in immune development and control of microbial infections, but their presence on dendritic cells has not been reported. We investigated whether extracellular ATP could trigger P2Z/P2X7receptor-dependent apoptosis of dendritic cells. Apoptosis could be selectively triggered by tetrabasic ATP, since other purine/pyrimidine nucleotides were ineffective, and it was mimicked by the P2Z receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
157
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(169 citation statements)
references
References 48 publications
10
157
1
1
Order By: Relevance
“…We also find three other bands marked by the anti-P2X 7 antibody, with lower molecular weights. In this experiment, positive control with macrophage cells, which have endogenous expression of P2X 7 homomeric receptors [11], confirms the band corresponding to the P2X 7 subunit at approximately 70 kDa. Therefore, Leydig cells endogenously express the classical P2X 7 subunits and other P2X 7 subunits probably derived from alternative splice.…”
Section: Discussionsupporting
confidence: 76%
“…We also find three other bands marked by the anti-P2X 7 antibody, with lower molecular weights. In this experiment, positive control with macrophage cells, which have endogenous expression of P2X 7 homomeric receptors [11], confirms the band corresponding to the P2X 7 subunit at approximately 70 kDa. Therefore, Leydig cells endogenously express the classical P2X 7 subunits and other P2X 7 subunits probably derived from alternative splice.…”
Section: Discussionsupporting
confidence: 76%
“…A third type of receptor is the unselective pore-forming P2X7 receptor, which is activated by ATP in the millimolar range and selectively inhibited by oxyATP (28). P2X7 is involved in Ag presentation and apoptosis of murine DC (13,16). Because oxyATP was not antagonistic in our experiments, the P2X7 receptor appears not to be involved in the activation of human DC.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, it has been shown that DC express P2 receptors, but their physiological role is unclear. Proposed functions include improved Ag presentation (13), cytokine production (14), chemotaxis (15), and induction of apoptosis (16).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…In addition, stimulation of P2Y 2 receptors in C6 glioma cells (28) and/or P2Y 4 receptors in rat glomerular mesangial cells can induce proliferation (29). At present apoptosis initiated by nucleotides is known only for a P2X receptor, being a prominent consequence of P2X 7 receptor activation in human macrophages and leukocytes as well as in mesangial, dendritic, and microglial cells (30,31). As with most examples of apoptosis, the P2X 7 receptor-initiated cascade, which includes the coupling of the ion channel to the SAPK-signaling cascade (32), involves a defined sequence of phenotypic changes that culminate in death only several hours after the exposure to ATP.…”
mentioning
confidence: 99%